The mentoring manual : your step-by-step guide to being a better mentor - Starr, Julie (Pearson, 2021)
Julie Starr is an expert and thought leader in the field of coaching. Since 2002, her best-selling book The Coaching Manual has supported the evolution of the coaching profession through simple, powerful principles and practical approaches. Her books are translated into many languages and are required reading on coach training programmes around the world. With over 20 years and thousands of hours coaching experience, Julie supports CEO’s and executives from the world’s largest organizations. Her approach is challenging, compassionate and empowers clear leadership.